Proses Pelaksanaan Pemberian Hak Restitusi Bagi Anak yang Menjadi Korban Tindak Pidana pada Tahap Penyidikan, Penuntutan dan Putusan Pengadilan - Novrianto, M.; Indrajaya, Indrajaya (Wajah Hukum, 2023)
The form of protection given to children is not optimal, where the law only provides protection in the form of imposing prison sanctions on perpetrators of crimes, while the fundamental rights of children who are victims of crime have not been taken seriously. The form of protection in question is a form of protection after the occurrence of a crime that has a direct effect on the victim, one of which is the granting of the right of restitution. The granting of the right of restitution is a form of compensation for children who are victims of a crime. qualitative in nature to obtain descriptive results.